Efficacy of assistive technology interventions - Edyburn, Dave L. (Emerald, 2015)
The Advances in special education technology series is designed to focus international attention on applications of technology for individuals with disabilities. Outstanding researchers from around the world will contribute chapters synthesizing the research evidence on specific types of technology interventions that improve access, engagement, and learning outcomes of diverse learners. The scope of contributions will cover subfields known as assistive technology, instructional design, instructional technology, online learning, personalized learning, and universal design for learning and will encompass both formal (i.e., school) and informal learning settings (i.e., self-directed, museums) across the lifespan (i.e., preschool - adult).
Keywords: Education -- Special Education -- General.; Teaching of students with specific learning difficulties/needs.; Self-help devices for people with disabilities.; Rehabilitation technology.; elektronické knihy; electronic books